Development of test method for anti-amoebic activity - Boo, Chie Yi (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study was carried out to obtain preliminary data of anti-amoebic screening test using non-pathogenic free living amoebae (FLA) and thus develop an appropriate preliminary test method for anti-amoebic activity. The anti-amoebic screening test was performed by treating free living amoebae with amino acid-thiourea derivative at concentration of 50 µg/mL. The viability of amoebae was examined and compared with the treatment thiourea control and NaCl cytotoxicity control at the same concentration. The number of viable FLA was calculated from the first 50 FLA that observed using inverted microscope with 100x magnification. One-way ANOVA was used to statistically analyse the data and Fisher‟s Least Significant Difference (LSD) test was conducted to analyse the significant data. Results of amino acid-thiourea derivative treatment showed potential anti-amoebic activity against non-pathogenic FLA. Test model of anti-amoebic activity was established and further studies can be carried out by using the same compound at different concentration levels.